Immunogenicity of Reduced-Dose Monovalent Type 2 Oral Poliovirus Vaccine in Mocuba, Mozambique. (12th November 2020) - de Deus, Nilsa; Capitine, Igor Paulo Ubisse; Bauhofer, Adilson Fernando Loforte; Marques, Selma; Cassocera, Marta; Chissaque, Assucênio; Bero, Diocreciano Matias; Langa, José Paulo; Padama, Fernando Manuel; Jeyaseelan, Visalakshi; Oberste, M Steven; Estivariz, Concepcion F; et al.
Abstract: Background: The monovalent type 2 oral poliovirus vaccine (mOPV2) stockpile is low. One potential strategy to stretch the existing mOPV2 supply is to administer a reduced dose: 1 drop instead of 2. Methods: We conducted a randomized, controlled, open-label, noninferiority trial (10% margin) to compared immunogenicity after administration of 1 versus 2 drops of mOPV2. We enrolled 9–22-month-old infants from Mocuba district of Mozambique. Poliovirus neutralizing antibodies were measured in serum samples collected before and 1 month after mOPV2 administration. Immune response was defined as seroconversion from seronegative (<1:8) at baseline to seropositive (≥1:8) after vaccination or boosting titers by ≥4-fold for those with titers between 1:8 and 1:362 at baseline. The trial was registered at anzctr.org.au (no. ACTRN12619000184178p). Results: We enrolled 378 children, and 262 (69%) completed per-protocol requirements. The immune response of mOPV2 was 53.6% (95% confidence interval, 44.9%–62.1%) and 60.6% (52.2%–68.4%) in 1-drop and 2-drop recipients, respectively. The noninferiority margin of the 10% was not reached (difference, 7.0%; 95% confidence interval, −5.0% to 19.0%). Conclusion: A small loss of immunogenicity of reduced mOPV2 was observed. Although the noninferiority target was not achieved, the Strategic Advisory Group of Experts on Immunization recommended the 1-drop strategy as a dose-sparing measure if mOPV2 supplies deteriorate further. Abstract : Immunization with 1 drop instead of the customary 2 drops of monovalent type 2 oral poliovirus vaccine results in only slightly reduced immunogenicity; this approach should be considered to stretch a limited supply of this vaccine when responding to outbreaks.